Productividad de las principales especies gramíneas forrajeras mejoradas del trópico ecuatoriano en condiciones de secano. - Guillen Arellano, Darley Antonio (2022)
The present work of practical component of complex examination was carried out with the objective of describing the productivity of the main improved forage grass species of the Ecuadorian tropics in dry conditions. The methodology used for the development of the work is descriptive, through the investigation of texts, magazines, theses, virtual libraries and scientific articles, which facilitated the respective ordering, analysis and summary. Livestock productivity depends on four fundamental factors that are: adequate management that has to do with the type of grass and animal load; the physical and nutritional characteristics of the soils (texture, structure, real density, depth, pH, percentage of organic matter and nutrients); the climate (precipitation, relative humidity and temperature) and finally the food that is nothing more than the type of food in sufficient quantities and of good quality. The use of improved species or varieties of pastures in the tropics under drought conditions is one of the main mechanisms through which livestock production and productivity have been increased, but their selection must be careful, and they must be previously subjected to a local evaluation, before its establishment. The research carried out allows us to improve the knowledge of the rancher in terms of optimizing the productivity of their pastures in dry seasons where in most tropical areas there is no availability of irrigation. The limited development of livestock in the Ecuadorian tropics is due in large part to its management, since grasslands with large extensions of free grazing are established on medium and low fertility soils, lacking irrigation systems and without greater contribution of technologies, depending essentially on the climatic conditions at each time of the year.